PENGEMBANGAN BAHAN AJAR BILINGUAL KIMIA DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI POKOK BAHAN KIMIA RUMAH TANGGA DI SMP NEGERI 1 BANJARMASIN - Dyah Ayu Riana; Maya Istyadji; Parham Saadi (Universitas Lambung Mangkurat, 2015)
Abstract. The research development of bilingual teaching material chemistry with contextual approach to the subject matter household chemical materials was studied. The aim of this research development was produced the product bilingual teaching material chemistry with contextual approach to the subject matter household chemical materials to support bilingual learning strategies and according to contextual learning steps. The model of the development refered to Dick & Carey model approach system. Expert tes subject was lecturer of FKIP UNLAM Banjarmasin, they were 3 lecturers of chemistry department as expert of matter and 2 lecturers of english department as expert of english. Meanwhile tryout subject were students of grade VIII in Junior High School 1 Banjarmasin year 2012/2013, they were 15 students of grade VIII that determined by randomly as small group tryout and 31 students of grade VIII A as field tryout. Data collection techniques were used a questionnaire sheet validation for expert of matter and english, observation sheet, achievement test, and students response. All of the data of the research were analyzed descriptively. The result of the research indicates that has been developed a bilingual teaching material chemistry with contextual approach to the subject matter household chemical materials which is valid and effective for increasing conceptual comprehension and english competence of students.